Effect of the scale resolution on the two phase coupling characteristics of high speed evaporating sprays using LES / Eulerian-Lagrangian methodologies. (November 2019) - Li, C.; Crua, C.; Vogiatzaki, K.
Highlights: Comprehensive evaluation of both the effect of the mesh structure and the grid resolution on two-phase flow modelling approaches using LES/Eulerian-Lagrangian frameworks. Establish relations between the droplet SMDs and the break-up coefficient (B1). The Stokes numbers in all cases are less than 1 (particles' motion tightly coupled to the gas phase) which makes the calculations prone to the selection of the break up model coefficient. Suggestion of the numerical Stokes number can play the role of an additional grid selection parameter. Abstract: The physics of high-speed liquid jets injected in elevated temperature and pressure conditions are extremely complex due to the multi-scale and multi-phase flow characteristics. Large eddy simulations (LES) are widely applied for simulations of multi-phase flows because large scale mixing of ambient gas with the liquid vapour (when evaporation is occurring) is better captured than other traditional computational fluid dynamics (CFD) techniques, such as Reynolds Averaged Navier-Stokes (RANS). However, in order for the LES predictions to be accurate, in addition to the required numerical accuracy of the solvers and the effect of the sub-grid scale (SGS) models, the mesh dependence needs to be addressed especially for large scale applications that the mesh resolution is never sufficient to capture all scale range. Although previous works have presented the effect the grid has on the accuracy of the simulation results of sprays based on a "trial and error" basis, no insight of the dynamics of each phase was provided in the same conditions under different grids. In our work the novelty lies in the fact that the observed trends of each phase regarding the mesh are explained based on the code numerics (OpenFOAM) and linked to the physics of the flow. Moreover, we investigate for the first time the dependence of the grid size on the mesh structure and the break up model coefficients. We aim to improve the understanding of the role of mesh refinement in multi-phase coupling characteristics and to provide a guideline for mesh resolution requirements within LES/Eulerian Lagrangian approaches not only for high speed evaporating sprays but also for more general problems where a continuous and disperse phase are present.